Advanced engineering mathematics - Wylie, C. Ray (McGraw-Hill, 1995)
This text aims to provide students in engineering with a sound presentation of post-calculus mathematics. It features numerous examples, many involving engineering applications, and contains all mathematical techniques for ngineering degrees. The book also contains over 5000 exercises, which range from routine practice problems to more difficult applications. In addition, theoretical discussions illuminate principles, indicate generalizations and establish limits within which a given technique may or may not be safely used.